INTEGRATION OF BLOCKCHAIN TECHNOLOGY IN THE FINANCIAL SYSTEM: ASSESSING ITS IMPACT ON EFFICIENCY, SECURITY, AND STABILITY OF FINANCIAL MARKETS - Loso Judijanto; Munir Tubagus; Renika Hasibuan; Duta Mustajab; Abdul Rosid (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Integrating blockchain technology into the financial system represents a pivotal advancement, initially conceived for Bitcoin but transcending its cryptocurrency origins. This paper comprehensively assesses its impact on financial market efficiency, Security, and stability. Examining historical development and case studies, the study delves into successful implementations, challenges faced, and lessons learned. Security implications are scrutinized, emphasizing blockchain's role in establishing immutable ledgers and protecting against fraud. Stability considerations focus on decentralization, evaluating its contributions to system resilience and transparency. A critical assessment highlights gaps, limitations, and unexplored potentials in current implementations, guiding further research. In conclusion, the paper emphasizes the intricate balance between benefits and challenges, advocating for adaptive regulations, technological refinements, and ongoing public education to integrate blockchain's transformative potential into the financial domain seamlessly.